Implementation of the STAD cooperative learning model in increasing student learning motivation in Islamic Religious Education lessons at a Junior High School - Maulana, Meiviani Nurul Aisyah; As-Syahida, Salma Nadhifa; Koestanti, Melinda; Asridayani, Asridayani; Nursobah, Asep (Jurnal Iman dan Spiritualitas, 2025)
This study aims to analyze the implementation of the Student Teams Achievement Division (STAD) cooperative learning model in enhancing students’ learning motivation in Islamic Religious Education (PAI) at SMP Plus Nurul Hidayah Pasundan. Employing a descriptive qualitative method, data were collected through classroom observation and documentation. The data were analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the STAD model fosters a collaborative, democratic, and pedagogically meaningful learning environment. Students demonstrated increased learning motivation, evidenced by active participation, enthusiasm in group discussions, and improved formative assessment outcomes. Theoretically, these results reinforce the principles of positive interdependence and individual accountability within cooperative learning frameworks. Practically, the implementation of STAD facilitates the internalization of Islamic values such as solidarity (ukhuwah), responsibility, and deliberation (mushawarah), while also serving as a relevant pedagogical alternative for character education in the 21st century. This research contributes to the development of contextual and value-based Islamic Religious Education models and positions STAD as a cross-cultural pedagogical strategy that supports the formation of intelligent, critical, and morally grounded Muslim students.